Pediatric athletes' ECG and diagnostic performance of contemporary ECG interpretation criteria. (15th July 2021) - Halasz, Geza; Cattaneo, Mattia; Piepoli, Massimo; Romano, Silvio; Biasini, Vincenzo; Menafoglio, Andrea; Gasperetti, Alessio; Badini, Matteo; Villa, Michele; Dall'Ara, Lorenzo; Roberto, Marco; Cassina, Tiziano; et al.
Abstract: Background: Electrocardiographic (ECG) pre-participation screening(PPS) can prevent sudden cardiac death(SCD) but the Interpretation of the athlete's ECG is based on specific criteria addressed for adult athletes while few data exist about the pediatric athlete's ECG. We aimed to assess the features of pediatric athletes' ECG and compared the diagnostic performance of 2017 International ECG recommendation, 2010 European Society of Cardiology recommendation and 2013-Seattle criteria in detecting clinical conditions at risk of SCD. Methods: 886 consecutive pediatric athletes (mean age 11.7 ± 2.5 years; 7–16-years) were enrolled and prospectively evaluated with medical history, physical examination, resting and exercise ECG and transthoracic echocardiography during their PPS. Results: The most common physiological ECG patterns in pediatric athletes were isolated left ventricular hypertrophy criteria (26.9%), juvenile T-wave pattern (22%) and early repolarization pattern (13.2%). The most frequent borderline abnormalities were left axis deviation (1.8%) and right axis deviation (0.9%) while T-wave inversion (0.8%) especially located in inferior leads (0.7%) was the most prevalent abnormal findings. Seven athletes (0.79%) were diagnosed with a condition related to SCD. Compared to Seattle and ESC, the International improved ECG specificity (International = 98% ESC = 64% Seattle = 95%) with lower sensitivity (ESC and Seattle 86%vs International 57%). The false-positive rate decreases from 36% of ESC to 2.2% of International but the latter showed a higher false-negative rate(0.34%). Conclusion: Pediatric athletes like the adult counterpart exhibit a high prevalence of ECG abnormalities mostly representing training-related ECG adaptation. The International criteria showed a lower false-positive rate but at the cost of loss of sensitivity. Highlights: Pediatric athletes have a high prevalence of ECG abnormalities representing training-related ECG adaptation. The Seattle criteria demonstrated the best balance between improvement in specificity and loss of sensitivity. Complete Right Bundle Branch Block should be considered an abnormal findings in pediatric athletes. International criteria showed the higher specificity compared with ESC-2010 and Seattle Criteria.